(untitled) (Proceedings of the Global Public Health Conference, 2023)
The emerging epidemic of COVID-19 Associated Mucormycosis(CAM) has been recognized as a significant global public health threat. India accounted for majority of the globally detected CAM cases especially during the second wave of the pandemic in 2021. A severe form of invasive CAM called Rhino-orbital-cerebral mucormycosis (ROCM) led to high mortality and morbidity especially in COVID patients with predisposing factors causing immunosuppression such as diabetes mellitus, malignancies, and steroid therapy. This study was carried out to describe the demographic features as well as analyze the comorbidities and outcomes of patients diagnosed with CAM and to provide an umbrella review of published global systematic reviews on CAM with special reference to ROCM. In this case series report, we have noted the findings and outcomes of 12 COVID patients with CAM treated at two different tertiary care hospitals in India. All were males, with an average age of 54.25 years. 66.6% had invasive ROCM and 91.7% had poorly controlled diabetes. All received liposomal amphotericin B, 58.3% underwent surgical interventions and the mortality rate was 33.3%. We also conducted an umbrella review of systematic reviews reported from 2020-2022. PubMed, Embase, Scopus and Google scholar databases and the PRISMA 2020 checklist were used to refine retrieval and review based on our study criteria. Common patterns were noted regarding the predisposing factors and treatment outcomes. Good glycemic control, the regulated use of steroids, proper decontamination of oxygen cylinders and the hospital environment as well as avoidance of overzealous use of steam inhalation have been proposed as important measures to control this epidemic.